Exposure to particulate matter in traffic: A comparison of cyclists and car passengers - Int Panis, Luc; de Geus, Bas; Vandenbulcke, Grégory; Willems, Hanny; Degraeuwe, Bart; Bleux, Nico; Mishra, Vinit; Thomas, Isabelle; Meeusen, Romain (Atmospheric environment (1994), 2010)
Emerging evidence suggests that short episodes of high exposure to air pollution occur while commuting. These events can result in potentially adverse health effects. We present a quantification of the exposure of car passengers and cyclists to particulate matter (PM). We have simultaneously measured concentrations (PNC, PM2.5 and PM10) and ventilatory parameters (minute ventilation (VE), breathing frequency and tidal volume) in three Belgian locations (Brussels, Louvain-la-Neuve and Mol) for 55 persons (38 male and 17 female). Subjects were first driven by car and then cycled along identical routes in a pairwise design. Concentrations and lung deposition of PNC and PM mass were compared between biking trips and car trips. Mean bicycle/car ratios for PNC and PM are close to 1 and rarely significant. The size and magnitude of the differences in concentrations depend on the location which confirms similar inconsistencies reported in literature. On the other hand, the results from this study demonstrate that bicycle/car differences for inhaled quantities and lung deposited dose are large and consistent across locations. These differences are caused by increased VE in cyclists which significantly increases their exposure to traffic exhaust. The VE while riding a bicycle is 4.3 times higher compared to car passengers. This aspect has been ignored or severely underestimated in previous studies. Integrated health risk evaluations of transport modes or cycling policies should therefore use exposure estimates rather than concentrations.